Measuring thermal load in fiber amplifiers in the presence of transversal mode instabilities - Beier, Franz; Ploetner, Marco; Sattler, Bettina; Stutzki, Fabian; Walbaum, Till; Liem, Andreas; Haarlammert, Nicoletta; Schreiber, Thomas; Eberhardt, Ramona; Tuennermann, Andreas (Optics Letters, 2017)
We report on detailed in situ distributed temperature measurements inside a high power fiber amplifier. The deducted thermal load and the transversal mode instability (TMI) threshold of a commercial large mode area fiber with 25 μm core and 400 μm cladding were measured at various seed wavelengths. By matching these results with detailed simulations we show that photodarkening has a negligible impact on the thermal load and, therefore, on the TMI threshold in this fiber.
CRIS-Team Scopus Importer:2023-04-20